Activating transcription factor 4: a regulator of stress response in human cancers - Wu, Di; Liang, Jie (Frontiers in Cell and Developmental Biology, 2024)
Activating transcription factor 4 (ATF4) is an adaptive response regulator of metabolic and oxidative homeostasis. In response to cellular stress, ATF4 is activated and functions as a regulator to promote cell adaptation for survival. As a transcriptional regulator, ATF4 also widely participates in the regulation of amino acid metabolism, autophagy, redox homeostasis and endoplasmic reticulum stress. Moreover, ATF4 is associated with the initiation and progression of glioblastoma, hepatocellular carcinoma, colorectal cancer, gastric cancer, breast cancer, prostate cancer and lung cancer. This review primarily aims to elucidate the functions of ATF4 and its role in multiple cancer contexts. This review proposes potential therapeutic targets for clinical intervention.